2022
DOI: 10.3390/jcm11102875
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Disgust Cognitive Behavioral Therapy for Contamination-Based Obsessive Compulsive Disorder: A Randomized Controlled Clinical Trial

Abstract: Background: Disgust is a strong and persistent emotion that frequently occurs during exposure-based treatments for contamination-based obsessive compulsive disorder (C-OCD). This study aimed to examine the efficacy of augmenting cognitive behavioral therapy (CBT) with a novel type of anti-disgust cognitive intervention in reducing the severity of OCD, disgust propensity/sensitivity, and refusal rate of exposure and response prevention, while simultaneously increasing acceptance of disgust. Materials and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…( 61 ), the present study showed that self-efficacy scores in FIM+ at T1 were meaningfully associated with reducing OCS at T2. It is unclear to what extent these results could generalize to patients with OCD, and we suggest future studies examine the role of health beliefs on response to treatment in this sample (e.g., 62 ).…”
Section: Discussionmentioning
confidence: 92%
“…( 61 ), the present study showed that self-efficacy scores in FIM+ at T1 were meaningfully associated with reducing OCS at T2. It is unclear to what extent these results could generalize to patients with OCD, and we suggest future studies examine the role of health beliefs on response to treatment in this sample (e.g., 62 ).…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, there are many studies in the literature that support the hypothesis that one of the main psychopathological factors in OCD is precisely disgust [12,37]. Further, a recent meta-analysis showed that ON symptoms are more related to EDs compared to OCD suggesting that ON might belong to the rst spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are many studies in the literature that support the hypothesis that one of the main psychopathological factors in OCD is precisely disgust [7,55]. Further, a recent meta-analysis showed that ON symptoms are more related to EDs compared to OCD suggesting that ON might belong to the rst spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, clinicians and researchers have not clari ed whether ON pertains to eating disorders (EDs) [3,4] or the obsessive-compulsive disorder (OCD) spectrum [5,6]. OCD, especially contamination-related OCD, is characterized by a heightened experience of disgust [7,8].…”
Section: Introductionmentioning
confidence: 99%